A qualitative exploration of stigma experience and inclusion among adults with mild to moderate intellectual disability in an Indonesian context. (June 2022) - Handoyo, Restu; Ali, Afia; Scior, Katrina; Hassiotis, Angela
Background: People with intellectual disability are among the most stigmatised groups in society. There is a paucity of studies reporting on how stigma is experienced in low- and middle-income countries. This study aims to explore the experience of stigma among adults with mild/moderate intellectual disability and the extent of their inclusion in Indonesian society. Method: Fifteen adults with mild/moderate intellectual disability were purposively recruited from three service providers and were interviewed using a semi-structured interview schedule. The data were analysed using thematic analysis. Results: The findings suggest that adults with intellectual disability experience stigma in multiple settings (family, school, community), have limited access to social activities, and internalised the experienced stigma. Conclusion: This study adds to the international understanding of stigma experienced by adults with mild/moderate intellectual disability in daily life and their inclusion in society in a middle-income country.